Memory and popular film - Grainge, Paul (Manchester University Press, 2003)
'Memory and popular film' uses memory as a specific framework for the cultural study of film. Taking Hollywood as its focus, this timely book provides a sustained, interdisciplinary perspective on memory and film from early cinema to the present. Considering the relationship between official and popular memory, the politics of memory, and the technological and representational shifts that have come to effect memory's contemporary mediation, the book contributes to the growing debate on the status and function of the past in cultural life and discourse. By gathering key critics from film studies, American studies and cultural studies, 'Memory and popular film' establishes a framework for discussing issues of memory IN film and of film AS memory. Together with essays on the remembered past in early film marketing, within popular reminiscence, and at film festivals, the book considers memory films such as Forrest Gump, Lone Star, Pleasantville, Rosewood and Jackie Brown. 'Memory and popular film' provides a wide-ranging analysis that will benefit both students and critics of popular culture, film studies and the past.